The determination of optimum ratio by using recycled concrete aggregate and crumb rubber as partial sand replacement material in sand cement brick production - F.S. Khalid (Universiti Malaysia Perlis (UniMAP), 2022)
Link to publisher's homepage at http://ijneam.unimap.edu.my